1993
DOI: 10.1161/01.cir.88.3.1245
|View full text |Cite
|
Sign up to set email alerts
|

Role of K+ATP channels in coronary vasodilation during exercise.

Abstract: These data demonstrate that K+ATP channels modulate coronary vasomotor tone under resting conditions and contribute to coronary vasodilation during ischemia. However, the coronary vasculature retains the capacity to dilate in response to increases in oxygen demand produced by exercise when K+ATP channels are blocked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
107
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 26 publications
9
107
1
3
Order By: Relevance
“…The experimental protocol described above was repeated in the diabetic animals at least 7 days after the alloxan injection with and without glibenclamide. In addition, three experiments were also conducted at rest and during exercise with glibenclamide in nondiabetic dogs to confirm the previous findings that K ATP channels are not required for exercise-induced coronary vasodilation (3)(4)(5)7,8). Assessing the relationship between coronary blood flow and myocardial metabolism.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…The experimental protocol described above was repeated in the diabetic animals at least 7 days after the alloxan injection with and without glibenclamide. In addition, three experiments were also conducted at rest and during exercise with glibenclamide in nondiabetic dogs to confirm the previous findings that K ATP channels are not required for exercise-induced coronary vasodilation (3)(4)(5)7,8). Assessing the relationship between coronary blood flow and myocardial metabolism.…”
mentioning
confidence: 67%
“…These studies indicate that K ATP channels are important in regulating coronary vascular resistance under baseline conditions (3-10), during hypoxic coronary vasodilation (11,12), and during reactive coronary hyperemia (1,4,13). However, it does not appear that K ATP channels are required to increase coronary blood flow when myocardial metabolism is increased (3)(4)(5)7,8).Recently, Kersten et al (14) found that diabetes enhanced K ATP channel-mediated coronary vasodilation of coronary arterioles, suggesting that K ATP channels are important in local metabolic coronary vasodilation in diabetes. Supporting this notion are the results of Shimoni et al (15) showing that the half-maximal inhibitory concentration (IC 50 ) for ATP-dependent inhibition of K ATP channels was approximately twofold higher for channels from diabetic rat hearts.…”
mentioning
confidence: 99%
See 3 more Smart Citations